Available chlorine consumption from NaOCl solutions passively placed in instrumented human root canals. (28th July 2014) - Ragnarsson, K. T.; Rechenberg, D. K.; Attin, T.; Zehnder, M.
Abstract Aim To monitor chlorine consumption from nonagitated aqueous sodium hypochlorite (NaOCl) solutions in human root canals using a recently developed assay, which can determine the order of magnitude of available chlorine in small volumes of liquid. Methodology The root canals of 80 extracted single‐rooted human teeth were instrumented to ProTaper Universal F4 and irrigated using 1% NaOCl. Subsequently, canals were irrigated with copious amounts of deionized water to rinse out the residual chlorine. Subsequently, the teeth were sealed externally and placed in a water bath of 37 °C. Root canals were filled with NaOCl of 1%, 2.75%, 5.5%, or distilled water for 1, 10, 100 or 1000 min (n = 5 teeth per solution and time). Consumption of chlorine was measured using paper points pre‐impregnated with 15% potassium iodide. Colour change of the paper points was determined photo‐electronically, assessing their red value after absorbing solutions from root canals. Measurements were compared to a standard series of NaOCl down to 0.001% (n = 5 paper points per concentration). Results Red values of the paper points inserted into the root canal were affected by initial NaOCl concentration and time (two‐way anova, P < 0.05). If NaOCl concentrations above 0.1% are considered to be clinically relevant, then 5.5% NaOCl retained its activity in the root canal for more than 100 min, whereas 1% NaOCl lost its activity between 10 and 100 min. Conclusions Nonagitated NaOCl solutions can remain biologically active in human root canals for extended time periods.